O património abandonado da Fábrica da Chicória. Circunstância, registo e transformação - Beatriz Tomé de Andrade Salvado Sousa (2019)
As architects we constantly draw over white canvas. The canvas already has a pre-established size, and their material has an effect on the finished product. But they are white, anyways. As an artist has trouble paiting over a finished paiting, an architect feels the same designing a project for an existing building. This study is born from that concern. Aiming awareness to the neglected buildings, in this case industrial ones, in Ribeira Grande, São Miguel. We try to question the role of the architect in this cases, where are the limits? The Chicory Factory is the main study case. An analysis is made based on different scales: island, county, parish and factory. In a way that a total site compreension is made. From the circumstance, in its many scales, there is a anotation of the actual state of the Factory and a understading on its old functions. At the same time, social environment and the way residents live takes an important role on the study. The final product is a design process, that tries to answer some of the questions who started the thesis, and some that apperead along the way.